IMPLEMENTASI UNDANG-UNDANG NEGARA REPUBLIK INDONESIA NOMOR 11 TAHUN 2008 TENTANG INFORMASI & TRANSAKSI ELEKTRONIK (UU ITE) TERHADAP REKAM MEDIS ELEKTRONIK (EMR) - Eriawan Agung Nugroho (Jurnal JURISTIC, 2020)
ABSTRAK Kemajuan teknologi informasi dimanfaatkan oleh manajemen rumah sakit untuk pengembangan Sistem Informasi Manajemen Rumah Sakit (SIMRS) yang terintegrasi. Tujuan utama SIMRS adalah efisiensi dan kecepatan pelayanan serta untuk pengambilan keputusan direksi, baik menyangkut keputusan terhadap masalah logistik, administrasi dan keuangan. Kemajuan ini telah melahirkan paradigma baru dalam manajemen informasi kesehatan termasuk didalamnya manajemen rekam medis elektronik (digital) yang telah merubah pola pikir dan pola tindak para praktisi profesi rekam medis, para ahli manajemen informasi kesehatan, para praktisi hukum dan para arsiparis (profesi kearsipan). Perubahan tersebut juga telah diikuti dengan penyesuaian dalam peraturan perundang-undangan, dimana Peraturan Menteri Kesehatan RI No. 749a tahun 1989 tentang rekam medis belum menyinggung mengenai rekam medis elektronik, sedangkan peraturan tentang rekam medis yang baru yaitu Peraturan Menteri Kesehatan RI No. 269/MENKES/PER/III/2008 telah terdapat aturan rekam medis elektronik. Dengan demikian Peraturan Menteri Kesehatan RI No. 269 Tahun 2008 tentang rekam medis ini menjadi dasar hukum penerapan rekam medis elektronik di Indonesia. Rekam medis elektronik adalah setiap catatan, pernyataan, maupun interpretasi yang dibuat oleh dokter atau petugas kesehatan lain dalam rangka diagnosis dan penanganan pasien yang dimasukkan dan disimpan dalam bentuk penyimpanan elektronik (digital) melalui sistem komputer. “Electronic Medical Record (EMR): an electronic sistem automate paper-base medical record”ABSTRACT Advancements in technology relating to the medical field has been a boon to medical professionals and hospital management alike in order to develop an integrated hospital information system (SIMRS). The goal of an integrated hospital management system (SIMRS) is to increase the speed and efficiency in which a hospital is able to provide medical care and in order for hospital management to be able to react faster to operational needs such as logistical issues, administrative needs, and financial actions. The advancement mentioned above has given way to the creation of a new paradigm in the field of information management which includes electronic medical bookkeeping (digital records) that have thus changed the viewpoints of medical practitioners, medical data analysts, legal practitioners, and archivists.Advancements in the field has also given rise to the need for the relevant laws to be adjusted. This is apparent in the ministry of health regulation No. 749a of the year 1989 regarding medical bookkeeping, which within its contents does not regulate about electronic medical bookkeeping and as such has been renewed into the ministry of health regulation No. 269/MENKES/PER/III/2008 which unlike its previous incarnation, has regulated the topic of electronic medical bookkeeping. This new law has become the principle rule in which all maters relating to electronic based medical bookkeeping is based upon The definition of an electronic medical record is the recording of any and all action relating to medical monitoring of a patient that ranges from notes taken of a patients current medical condition, statements given by doctors or ay other medical professional to a patient in order to diagnose and administer medical action, which is then stored in digital/electronic format with the use a computer. “Electronic Medical Record (EMR): an automated electronic system based medical record”